The Role of Accounting in Addressing Climate Change and Promoting Sustainable Development of SMEs in Indonesia - Dewi, Yuli (Eastasouth Institute, 2025)
This research explores the important role of accounting in promoting sustainability and addressing the challenges of climate change, particularly in Small and Medium Enterprises (SMEs) in Indonesia. SMEs are central to the Indonesian economy, contributing significantly to GDP and employment. However, they often face challenges in integrating sustainable practices due to limited resources, lack of awareness, and minimal regulatory pressure. Accounting is positioned as a key enabler in helping SMEs manage environmental costs, access green financing, and implement sustainability reporting frameworks. This paper examines how accountants can educate and advocate for sustainability, simplify reporting frameworks, and utilize digital tools to support SMEs in adopting climate-resilient practices. Practical examples, such as the case of a batik SME that reduced operational costs and secured a green loan through sustainable practices, demonstrate the tangible benefits of accounting-driven sustainability initiatives. The research concludes that accounting plays an important role in shaping a sustainable future, with SMEs serving as key players in the green economy. Accountants are instrumental in driving change by measuring, reporting and advocating for sustainable business practices.